Peningkatan kualitas hidup lansia penderita hipertensi melalui pelatihan self help group di posyandu lansia - Indriyati Indriyati; Vitri Dyah Herawati; Etty Eriyanti; Atik Aryani; Ni’mah Mufidah (Penamas: Journal of Community Service, 2026)
Hypertension is a complex genetic disease influenced by multiple genetic factors. Genetics accounts for 30% of blood pressure variation. Heredity or genetic predisposition to this disease is the most important risk factor, and there is a history of hypertension in the family. Research indicates that the family also greatly influences the condition of its descendants. The purpose of this activity is self-help group training and self-management for hypertension sufferers at the elderly posyandu in Ginung village to improve the quality of life of patients with hypertension. Implementation of community service activities in Ginung village, Gajahan, Colomadu includes: group formation, discussion and education sessions, supporting activities, evaluation, and monitoring. The service results include health education, with the majority in the sufficient category (15 people, 45.5%); after the activity, the majority experienced an increase in the good category (18 people, 54.5%). Self-help group training activities for elderly people with hypertension, to create a sense of enthusiasm for life, and self-management to improve the quality of life of elderly people with hypertension.